Intra-abdominal multi-organ involvement of kaposiform hemangioendothelioma in a child with Kasabach–Merritt phenomenon and contrast-enhanced ultrasound findings: a case report - Luo, Shu; Chen, Anjie; Zhou, Jiaojiao; Ji, Yi; Jin, Shuguang; Liu, Juxian (Frontiers in Medicine, 2025)
BackgroundKaposiform hemangioendothelioma (KHE) is a rare, locally aggressive vascular tumor that occurs in infancy and early childhood and is associated with significant morbidity. A severe complication of KEH is Kasabach–Merritt phenomenon (KMP), a life-threatening consumptive coagulopathy accompanied by thrombocytopenia.Case presentationWe report a rare case of KHE complicated by KMP, with multifocal involvement of the pancreatic head, liver, biliary tract, and duodenal papilla. Contrast-enhanced ultrasound (CEUS) revealed characteristic imaging features of the pancreatic head lesion, demonstrating inhomogeneous hypoenhancement during the arterial and portal phases, followed by complete washout and absence of enhancement in the late phase.ConclusionAfter the failure of multiple therapeutic interventions, the patient successfully underwent a pancreatoduodenectomy. This case underscores that surgical resection should be considered for KHE when it is feasible and safe. Furthermore, recognizing the distinctive CEUS features of pancreatic KHE is crucial for accurate diagnosis and avoiding diagnostic pitfalls.